2015
DOI: 10.1097/sla.0000000000000851
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Clinical Coding Accuracy in Surgery

Abstract: The coded data are a key engine for knowledge-driven health care provision. They are used, increasingly at individual surgeon level, to benchmark performance. Surgical clinical coding is prone to subjectivity, variability, and error (SVE). Having a specialty-by-specialty understanding of the nature and clinical significance of informatics variability and adopting strategies to reduce it, are necessary to allow accurate assumptions and informed decisions to be made concerning the scope and clinical applicabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Furthermore, the diagnoses and procedures that appear in administrative data may be incomplete and may include errors. 17 , 18 …”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, the diagnoses and procedures that appear in administrative data may be incomplete and may include errors. 17 , 18 …”
Section: Limitationsmentioning
confidence: 99%
“…Such data might be more satisfactory in identifying surgical procedures, cancer, or rare diseases, but in conditions for which patients are most likely to be admitted to hospital acutely, coding accuracy is known to be poor. 11 14 31 Fourthly, as coding accuracy might differ between countries and healthcare systems, the coding related biases we reported using UK data might not be generalisable to other countries. Recent data from countries using different coding practices to the UK, however, also reported low sensitivity and positive predictive value with administrative data alone in identifying acute stroke.…”
Section: Discussionmentioning
confidence: 95%
“…Hospital reimbursement is based on the diagnosis and procedure codes recorded in HES, therefore there are incentives for these data to be comprehensively recorded. However, this is routine data so will inevitably contain data entry errors; for example, an audit between 2010 and 2013 found that 13% of primary diagnoses and 12% of primary procedures were coded incorrectly [ 22 ]. Our analysis only includes patients admitted to hospital so we cannot determine the incidence of ankle fractures managed non-surgically in the emergency department or in outpatient appointments.…”
Section: Discussionmentioning
confidence: 99%